2017
DOI: 10.31943/wej.v1i1.13
|View full text |Cite
|
Sign up to set email alerts
|

The Advantages of Youtube to Enhance Student’s Vocabulary in Mechanical Engineering Classroom

Abstract: Most of Mechanical Engineering students have very low interest and motivation towards English even they regard English as huge obstacle. Besides that, it is the lack of module or material of English especially for mechanical engineering. Because of this problem, English teaching in this class needs the materials or methods which is suitable for those students therefore the student learning experience is more interesting and challenging. This is the main reason why lecturers of vocational colleges especially fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 1 publication
0
3
0
2
Order By: Relevance
“…In addition, the reflection result concludes that there are some difficulties faced by the students in doing evaluation test of differential material in the form of definition, and also in doing the high level of differential test. Therefore, the cycle II was conducted by making a coordination with other lecturers as observers and implementing an innovative learning media in this case Mathematical Communication which was equipped by a dominant computation software and web (Qurohman, 2020;Qurohman & Bersama, 2017;Romadhon & Qurohman, 2017.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the reflection result concludes that there are some difficulties faced by the students in doing evaluation test of differential material in the form of definition, and also in doing the high level of differential test. Therefore, the cycle II was conducted by making a coordination with other lecturers as observers and implementing an innovative learning media in this case Mathematical Communication which was equipped by a dominant computation software and web (Qurohman, 2020;Qurohman & Bersama, 2017;Romadhon & Qurohman, 2017.…”
Section: Discussionmentioning
confidence: 99%
“…The findings showed that the materials can be considered as an incidental strategy to improve learners on their vocabulary knowledge of the target language. The use of an online platform involving audio-visual features on the student's vocabulary acquisition of mechanical terms among 30 vocational students was presented by Romadhon and Qurohman (2017). The study performed materials taken from YouTube within two cycles or stages.…”
Section: Multimedia and Related Work In The English Language Classroomsmentioning
confidence: 99%
“…15. Out of these papers, several studies highlighted the increase in confidence (32.1%) [180], [181], communication competencies (21.4%) [182], [183], creativity (14.3%) [184], [185], teamwork [186], [187], critical thinking [188], [189], problem solving [190], [191], and ethical thinking [192]. On the contrary, only few papers highlighted that YouTube videos do not affect students' competencies such as problem-solving abilities [193].…”
Section: ) Enhancing Various Competenciesmentioning
confidence: 99%